Swimmer's shoulder - A basic guide - Pollard, B. (2001)
The following is a very simple and basic guide for swimmer's to use and follow regarding shoulder pain they may experience through swimming training. Recent studies (e.g. Pollard, 2001) have shown that up to 83% of senior and 53% of age group competitive swimmers have suffered shoulder pain at some point during their career. With proper care and attention, shoulder pain can be avoided; however, without the correct knowledge and treatment shoulder pain can ruin careers, greatly hasten retirement and hinder performance. Content: - What is "Swimmers Shoulder"? - What does it feel like? - What can I do to help? - What activities should I avoid? - Is there anything I can do to help prevent "Swimmers Shoulder"